Role of Bacterial Consortium and Synthetic Surfactants in Promoting the Phytoremediation of Crude Oil-Contaminated Soil Using Brachiaria mutica - Anwar-ul-Haq, Muhammad; Ibrahim, Muhammad; Yousaf, Balal; Al-Huqail, Asma A.; Ali, Hayssam M. (Frontiers in Energy Research, 2022)
Crude oil is causing widespread pollution in both aquatic and terrestrial environments. Phytoremediation, which is an emerging technology, involves the efficient use of plant species to remove, detoxify, and/or immobilize contaminants in the soil through natural processes. For this study, Para grass (Brachiaria mutica) inoculated with a previously isolated and characterized bacterial consortium was grown in a pot containing crude oil-contaminated soil. The effects of different concentrations (0.01, 0.1, and 1% of 10% detergent solution in ultrapure water) of nonionic surfactant (Triton X-100) on the degradation of crude oil in contaminated soil were observed. After 4-month experimentation, the maximum growth of the plant root length (28.57 cm), shoot length (65.73 cm), and dry biomass of root and shoot (92.42 g) in the pot having an application of surfactants of 0.1% augmented with the bacterial consortium (T7) was observed. Increasing the concentration of Triton X-100 from 0.01 to 1% augmented with a bacterial consortium led to the maximum removal of total petroleum hydrocarbons ranging between 6 and 40%. This is an indication of the inhibiting effect of Triton X-100 above 0.1% on the growth of plants. Furthermore, the hydrocarbon degradation was confirmed by the FTIR study that can be attributed to the adopted plant species' ability to degrade crude oil contamination, and it is evident through the FTIR results after 120 days of experimentation that the different functional groups are responsible for petroleum hydrocarbons present in soil samples. The current study concludes that the application of integrated treatment of crude oil-contaminated soil by using Triton X-100 and augmented with microbes can help to restore polluted soils for agricultural use. Future strategies such as bioaugmentation of contaminated soil with PGPR and the use of genetically modified (GMO) plants may result in amplifying plant tolerance and ultimately lower the level of soil pollutants for better soil health and boost plant yield.